2017
DOI: 10.1088/1361-6501/aa8ba3
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed compact magnetic sector mass spectrometer

Abstract: In this paper, a novel compact magnetic sector mass spectrometer has been developed and tested at the Lanzhou Institute of Physics. Its design is based on the mass separation of a 90° magnetic sector-field analyzer with a double trajectory, which has a magnetic induction of 0.7 T. The instrument can record mass range from 1 to 50 amu based on two special trajectories when the accelerating voltage of the ion source changes from 200 V to 2500 V. The dimensions of the device together with the electronic unit are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…[30] designed a miniature EI source which employs two identical rhenium–tungsten filaments featuring longer lifetime and improved stability with a power consumption of 15 W. Meng et al. [31] developed the ionization chamber with a dimension of 12 × 12 × 7 mm 3 and an exit slit that is 1 mm wide. Yan et al.…”
Section: Instrumentation Of Portable Mass Spectrometersmentioning
confidence: 99%
See 3 more Smart Citations
“…[30] designed a miniature EI source which employs two identical rhenium–tungsten filaments featuring longer lifetime and improved stability with a power consumption of 15 W. Meng et al. [31] developed the ionization chamber with a dimension of 12 × 12 × 7 mm 3 and an exit slit that is 1 mm wide. Yan et al.…”
Section: Instrumentation Of Portable Mass Spectrometersmentioning
confidence: 99%
“…In addition to developing new filament materials, research efforts have also been made to optimize and reduce the size of the EI unit [29]. Li et al [30] designed a miniature EI source which employs two identical rhenium-tungsten filaments featuring longer lifetime and improved stability with a power consumption of 15 W. Meng et al [31] developed the ionization chamber with a dimension of 12 × 12 × 7 mm 3 and an exit slit that is 1 mm wide. Yan et al [32] reported that increasing the exit slit to 1.5 mm further improved the ionization efficiency.…”
Section: Electron Ionizationmentioning
confidence: 99%
See 2 more Smart Citations
“…6.1. Development of a Miniature Magnetic Sector MS. Aiming at space exploration, we have developed a series of mass spectrometers, including TOF MS [68][69][70], ion trap MS [71][72][73], and magnetic sector MS (MMS) [74][75][76], among which a miniature MMS has been constructed and launched to 499 km Earth's orbit along with an experiment satellite in 2012 [76]. Compared with other mass spectrometers, MMS's advantages lie in simplicity, stability, high mass resolution and mass rejection ratio, and superior abundance sensitivity, making it a selection for atmospheric composition analysis and isotopic analysis [77].…”
Section: Space Mass Spectrometermentioning
confidence: 99%